Actualization of peacekeeping activity priority directions in the conditions of current Russian-Ukrainian war on the example of police structures of the countries of the world and Ukraine - M. A. Akopyan (Bulletin of Kharkiv National University of Internal Affairs)
The issue of the effectiveness of peacekeeping educational processes on the basis of national patriotic education has been updated, taking into account global challenges and threats. It is proposed to create appropriate effective forms of education and science with emphasis on the training and retraining of peacekeeping personnel in the direction of conducting effective trainings, scientific research, lectures on various platforms (online auditoriums, amphitheatres, etc.). The formation of the necessary peacemaking skills is a guarantee of the stability of the state, especially regarding the unification around the solution of such issues as ecocide, genocide, modern states of war, ethnic hatred, racism, violence in the family, regarding the solution of various kinds of conflicts, communication and cooperation with issues of peace and security both in a separate country and in the world.